1999
DOI: 10.1093/jnci/91.17.1487
|View full text |Cite
|
Sign up to set email alerts
|

Race and Differences in Breast Cancer Survival in a Managed Care Population

Abstract: Among women with similar medical care access since before their diagnoses, we found ethnic differences in stage of breast cancer at diagnosis. Adjustment for this difference and for income, age, and marital status resulted in a negligible effect of race on survival.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
77
1

Year Published

2002
2002
2013
2013

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 131 publications
(85 citation statements)
references
References 27 publications
7
77
1
Order By: Relevance
“…[23][24][25][26][27][28][29] However, the results of the current study support results of a study by Wojcik et al 30 who reported that survival remains significantly worse for African-American women even with equivalent treatment. In the Wojcik et al study, survival was significantly better for patients who received BCS with radiation therapy than for those who received BCS alone.…”
Section: Discussionsupporting
confidence: 86%
“…[23][24][25][26][27][28][29] However, the results of the current study support results of a study by Wojcik et al 30 who reported that survival remains significantly worse for African-American women even with equivalent treatment. In the Wojcik et al study, survival was significantly better for patients who received BCS with radiation therapy than for those who received BCS alone.…”
Section: Discussionsupporting
confidence: 86%
“…Although biologic and behavioral differences may influence outcomes to some extent, evidence suggests that when women across racial and ethnic groups receive equal treatment, equal outcomes follow [97,98]. Black patients are at no greater risk for chemotherapy-related hematologic toxicity than white patients [99], and clinical trial results suggest that patterns of response to local and systemic therapy are similar for black and white women withclinicallyequivalentdisease[75, 100 -102].Inlightofthisevidence, it is critically important that the health system itself is designed in such a way that all women have access to lifeprolonging cancer treatments, regardless of race, age, or socioeconomic status.…”
Section: Opportunities and Recommendations For Future Researchmentioning
confidence: 99%
“…1,2 Later stage at diagnosis accounts for a significant proportion of the mortality difference, and lower rates of screening mammography account for some of the racial disparities in stage at diagnosis. [3][4][5] Although…”
Section: Interventionmentioning
confidence: 99%